Numerical simulation of negative streamers in strong non-uniform electric fields in nitrogen. Effect of needle radius and applied voltage on streamer velocity - Manuilenko, O.V.; Golota, V.I. (Плазменно-пучковый разряд, газовый разряд и плазмохимия, 2013)
The results of numerical simulations of the propagation of a negative streamer in nitrogen in the uniform and strongly non-uniform electric fields are presented. It is shown that the propagation velocity of the streamer in a nonuniform electric field is always higher than its velocity in an uniform field at given voltages on electrodes. It is shown that as the needle radius decreases, the velocity of the streamer increases. The growth of streamer velocity, with decrease of the needle radius, is stopped when the needle curvature radius reaches a certain critical size. It is shown that in the region of the strong nonlinearity, when the streamer dynamics is determined by the charge of the streamer head, its velocity as a function of the longitudinal coordinate is independent of the needle radius. It is shown that the velocity of the streamer increases with growth of the applied voltage. Наведено результати числового моделювання поширення негативного стримера в азоті в однорідних і сильно неоднорідних електричних полях. Показано, що швидкість поширення стримера в неоднорідному полі завжди більша його швидкості в однорідному полі при однакових потенціалах на електродах. Показано, що при зменшенні радіуса голки швидкість стримера збільшується при заданій напрузі на електродах. Зростання швидкості стримера, із зменшенням радіуса голки, припиняється, коли радіус кривизни голки досягає деякого критичного розміру. Показано, що в області сильної нелінійності, коли динаміка поширення стримера визначається його об'ємним зарядом, його швидкість, як функція поздовжньої координати не залежить від радіуса голки. Показано, що швидкість стримера зростає з ростом напруги, що прикладена до електродів. Приведены результаты численного моделирования распространения отрицательного стримера в азоте в однородных и сильно неоднородных электрических полях. Показано, что скорость распространения стримера в неоднородном поле всегда больше его скорости в однородном поле при одинаковых потенциалах на электродах. Показано, что при уменьшении радиуса иглы скорость стримера увеличивается при заданном напряжении на электродах. Рост скорости стримера, с уменьшением радиуса иглы, прекращается, когда радиус кривизны иглы достигает некоторого критического размера. Показано, что в области сильной нелинейности, когда динамика распространения стримера определяется его объемным зарядом, его скорость, как функция продольной координаты не зависит от радиуса иглы. Показано, что скорость стримера возрастает с ростом напряжения, приложенного к электродам.